Antiinflammatory evaluation of leaves of Plumeria acuminata - Gomathi P; Mazumder UK; Gupta M; Selvan V Thamil (BMC, 2006)
Abstract Backround Plumeria acuminata belonging to the family Apocynaceae is commonly known as 'perungalli' in Tamil and is widely distributed throughout the Southern parts of India. In traditional medicinal system different parts of the plant have been mentioned to be useful in a variety of diseases. The plant material is widely used as a purgative, remedy for diarrhoea and cure for itch. The milky juice is employed for the treatment of inflammation and rheumatism. The bark has been reported to be useful in hard tumors, diarrhoea and gonorrhoea. The objective of the present study was to evaluate the antiinflammatory activity of methanol extract of leaves of Plumeria acuminata on carrageenan, dextran, histamine and serotonin-induced inflammation in rat hind paw oedema models. Methods Acute and chronic inflammation models were used to evaluate the anti-inflammatory activity of the extract. Wistar albino rats of either sex weighing 180-200 g were used. In acute model carrageenan, dextran, histamine and serotonin models were used to induce inflammation in rat hind paw and cotton pellet-induced granuloma method was used for chronic inflammation model. In each model four groups of six animals were used. In all the models Group I served as control (0.9% normal saline, 5 mlkg-1 b.w) and group IV as standard (Indomethacin 10 mgkg-1 b.w). Group II and III received extract at the doses of 250 and 500 mgkg-1 b.w respectively. Results The methanol extract of Plumeria acuminata exhibited significant anti-inflammatory activity on the tested experimental animal models. The extract (500 mgkg-1 b.w) exhibited maximum antiinflammatory effect i.e., 30.51, 47.06, 34.48 and 32.50% (P < 0.001) at the end of 3 h with carrageenan, dextran, histamine and serotonin respectively. Administration of MEPA (500 mgkg-1 b.w) and indomethacin (10 mgkg-1 b.w) significantly reduced the formation of granuloma tissue induced by cotton pellet method at a rate of 45.06 and 51.57% respectively. The effect produced by the extract was comparable to that of indomethacin a prototype of a nonsteroidal antiinflammatory agent. Conclusion The results obtained in this study indicated that the methanol extract of Plumeria acuminata possess potent antiinflammatory activity in both acute and chronic models.